From the sidelines: The indirect repercussions of COVID‐19 on the delivery of hospital surgical services. Issue 7 (21st June 2021) - McBride, Kate E.; Steffens, Daniel; Solomon, Michael J.
Abstract: Background: Despite relatively few COVID‐19 cases within New South Wales, the uncertainty surrounding the pandemic has prevented a return to business as usual for the delivery of surgical services. This study aims to describe the evolving impact of COVID‐19 on surgical activity and patient outcomes at a major public tertiary referral hospital. Methods: A retrospective cohort study involving adult surgical patients treated at a large public tertiary referral hospital in Sydney, Australia. Surgical activity, surgical outcomes and patient demographics were compared across two time periods, including the 'first wave' (February–May 2020 vs. February–May 2019) and the 'perseverance phase' (June–September 2020 vs. June–September 2019). Variables across both groups were compared using an independent t test or chi‐squared test. Results: A −32% reduction in surgical separations was observed in the 'first wave', including −20% emergency and −37% elective. In the 'perseverance phase', there was a −19% reduction in surgical activity, including 0% emergency and −27% elective. The average length of stay, intensive care admissions, postoperative complications and in‐hospital costs significantly increased in the 'first wave'. The proportion of public patients increased marginally (3%) in the 'first wave'. Conclusion: The impact of COVID‐19 was most severely experienced in the initial months of the pandemic and observed in the number of patients treated. Although there was an initial effect on surgical outcomes, overall, the standard of care remained safe. The delivery of elective surgery remains a challenge and reflects the ongoing system‐wide changes that are required to manage the COVID‐19 pandemic. Abstract : The ongoing uncertainty surrounding the COVID‐19 pandemic has prevented a return to business as usual for the delivery of surgical services. The impact of COVID‐19 was most severely experienced in the initial 'first wave' of the pandemic (February to May 2020) and observed in the number of surgical patients treated. There was an initial effect on patient outcomes, however, overall the standard of care remained comparable and safe. The delivery of elective surgery remains a challenge and reflects the ongoing system‐wide changes that are required to manage the COVID‐19 pandemic.